Getting started with digital literacy using pedagogic corpora in young learners’ english classes - Dutra, Deise Prina; Marques, Ana Lúcia (The ESPecialist, 2023)
This paper addresses the provision of instruction to teachers and learners on becoming digitally literate and skilled with corpus-based tools. It proposes the compilation of specific pedagogic corpora, in this case in Geography and Science, to be used in the English young learners’ classes in elementary education.The paper also illustrates the handling of user-friendly concordancer’s tools of #LancsBox 6.0 to perform basic analysis of the corpora language through a more accessible technology. It concludes by summarizing the possible benefits of an alternative approach to expose learners to customized corpus-informed language in English.